Fluid Dynamics in a Continuous Pump-Mixer - Dominic Wirz; Simon Gründken; Anne Friebel; Kevin Rave; Mario Hermes; Romuald Skoda; Erik von Harbou; Hans-Jörg Bart (Applied Sciences, 2022)
The fluid dynamic (flow rates) and hydrodynamic behavior (local droplet size distributions and local holdup) of a continuous DN300 pump-mixer were investigated using water as the continuous phase and paraffin oil as the dispersed phase. The influence of the impeller speed (<semantics>N<mtext> </mtext></semantics>= 375 to 425 rpm), the feed phase ratio (<semantics>φF</semantics> = 10 to 30 vol.-%), and the flow rate (<semantics><mover accent="true">V˙</mover>tot</semantics> ≈ 0.5 to 2.3 L/min) were investigated by measuring the pumping height, local holdup of the disperse phase, and the droplet size distribution (DSD). The latter one was measured at three different vessel positions using an image-based telecentric shadowgraphic technique. The droplet diameters were extracted from the acquired images using a neural network. The Sauter mean diameters were calculated from the DSD and correlated with an extended model based on Doulah (1975), considering the impeller speed, the feed phase ratio, and additionally the flow rate. The new correlation can describe an extensive database containing 155 experiments of the fluid and hydrodynamic within a 15% error range.